ANTI-INFLAMMATORY ACTIVITY OF ETHANOLIC EXTRACT OF TARO LEAVES (Colocasia esculenta (L.) Schott) AND ITS FRACTIONS IN RATS USING EGG WHITE-INDUCED MODEL - Sujono, Tanti Azizah; Rahmawati, Desi (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Taro plant (Colocasia esculenta (L.) Schott) is empirically known to have anti-inflammatory activity. Taro leaves contain secondary metabolites such as alkaloids, saponins, tannins, flavonoids, and polyphenols. This study aimed to prove the anti-inflammatory effectiveness of ethanol extract of taro leaves (EETL), ethyl acetate fraction (EAFTL), and residual fraction (RFTL) in rats induced by 1% egg white solution, and to identify the chemical compound groups contained in EETL and its fractions. Thirty-two rats were divided into eight groups, namely group I as a negative control (CMC-Na 0.5%), group II as a positive control (Diclofenac sodium 4.5 mg/kgBW), groups III-IV were administered EETL 100 and 200 mg/kgBW, groups V-VI were administered EAFTL 100 and 200 mg/kgBW, and groups VII-VIII were administered RFTL 100 and 200 mg/kgBW. The animal models were induced with 0.1 mL of 1% egg white solution subplantar 1 hour after oral treatment. The volume of rat leg edema was measured every 1 hour for six consecutive hours. This research shows that EETL 100 mg/kgBW and RFTL doses of 100 and 200 mg/kgBW have an anti-inflammatory effect with a percent inhibitory power of >50%. Phytochemical screening showed that EETL contains alkaloids, saponins, tannins, and phenolics. EAFTL contains tannins and phenolics, whereas RFTL contains saponins, tannins, and phenolics. Keywords: Taro leaves, antiinflammatory, egg white solution, fractionation